Allelochemical composition and content of acrostichum aureum, stenochlaena palustris, and dicranopteris linearis - Othman, Rashidi; Ramya, Razanah; Mohd Hassan, Norazian (Nova Science Publishers, 2018)
The aim of this study was to investigate the presence of allelochemical composition and content from the fern leaves of Acrostichum aureum, Stenochlaena palustris and Dicranopteris linearis using maceration extraction method for further analysis of allelochemical. Total phenolic contents in extracts were determined by applying the Folin Ciocalteu assay and the functional group was determined by using FT-IR spectroscopy. The allelochemical compound screened by GCTOF-MS and phenolic acids content were detected by HPLC. The highest total phenolic content was in A. aureum (1129.52 ± 6.02 mg GAE/g DW), followed by S. palustris (938.68 ± 7.22 mg GAE/g DW) and D. linearis (699.82 ± 6.25 mg GAE/g DW). The FT-IR analysis had proven the presence of aliphatic hydrocarbon in three fern species. Meanwhile, the major active allelochemical that had been identified through GCTOF-MS in three fern species was Phenol, 2,4-bis (1,1-dimethylethyl) and only 2-Methoxy-4-vinylphenol was found in S. palustris. Seven phenolic acids implicated in fern allelopathy were analysed in HPLC which were 4-hydroxybenzoic acid, caffeic acid, vanillic acid, trans-p-coumaric acid, ferulic acid, 3-coumaric acid and 2-coumaric acid that had been identified and quantified by comparing with a standard reference. The composition of phenolic acids content was detected the highest in S. palustris leaf, meanwhile, only 4 phenolic acids detected in A. aureum and no phenolic acid detected in D. linearis. Thus, S. palustris and A. aureum leaves could be considered as a good source of phenolic acids as well as allelochemicals production.